ENHANCING HIGHER EDUCATION LITERACY THROUGH PEER-SHARING SOCIALIZATION: COMMUNITY SERVICE FOR SENIOR HIGH SCHOOL STUDENTS IN BANDA ACEH - Mutiara Ramadhani; Reva Fitri Syarly Usi; Liza Nasrah; Raisa Syihadina Zacvi; Diana Sapha A.H (CV. Naskah Aceh, 2026)
Many high school students in Indonesia lack access to accurate information about university study programs, which impedes informed career decision-making. This community service activity aimed to improve the knowledge and understanding of Grade XI students at MAN Model Banda Aceh regarding the profile, curriculum, student activities, and graduate career prospects of the Development Economics Study Program (EKP) at the Faculty of Economics and Business, Universitas Syiah Kuala (USK). A participatory socialization method was employed, encompassing structured presentations, group discussions, and interactive question-and-answer sessions, conducted on May 20, 2026. The activity engaged 42 students from the Grade XI Science class (IPA). Activity evaluation was conducted through direct observation of participant engagement, photographic documentation, and qualitative assessment of student participation during discussion and question-and-answer sessions. Results indicated high levels of enthusiasm and active participation, with students raising numerous substantive questions covering program distinctions, admission pathways, campus life, and graduate career prospects. These outcomes confirm that interactive, face-to-face program socialization is effective in broadening students’ educational literacy and supporting more informed career decision-making among secondary school students.